Agostinho e o ceticismo: um estudo da crítica agostiniana ao ceticismo em Contra Acadêmicos - Pereira Junior, Antonio (2012)
The assent of the Truth: here's a formula that seems to have puzzled philosophers since antiquity. The possibility of apprehending truth was defended by some philosophers who have been called dogmatic, due to their haste to judge appearances as representations of reality, and refuted by those who chose to continue questioning rather than engage with his predicament. These thinkers were called skeptics. Among those who defended the consent of the truth, is highlighted by St. Augustine in this research, which aims to combat the widespread skepticism in the ancient doctrine of the Academy of Plato in his work Against Academicos. Thus, to conduct this research we ask: What are the main arguments made by St. Augustine against the scholarly skepticism? In order to address the problem identified, we propose to investigate the critical skepticism of St. Augustine, identifying and analyzing the main rebuttals he built. For this purpose, we conducted a survey of aspects of both the skepticism about the life and thought of St. Augustine about this doctrine